Lending Diversification and Interconnectedness of the Syndicated Loan Market - Oh, Gabjin; Park, A-young (Frontiers in Physics, 2021)
We investigate the effects of syndicated loan network centrality on bank performance. Syndicated loan network centrality measures the similarity and influence of the other banks within a given banks network. The network centrality constructed by syndicated loans can allow banks to gather and transfer valuable information and can thus facilitate profit-making acquisition in loan investment decisions. We use a planar maximally filtered graph to construct an interbank network using syndicated loan portfolios at the industry level. We show that the syndicated loan portfolios of high-centrality banks exhibit a higher level of portfolio diversification than those of low-centrality banks. We also document that our composite centrality measure of the bank network showed statistical significance in terms of bank performance even after controlling for the financial variables of market size, loan allocation, total asset, and loan diversification. Our findings suggest that the performance of a bank in a syndicated loan hierarchy is related to its position in this hierarchy.